PELATIHAN PENANGANAN PASIEN GAWAT DARURAT YANG EFEKTIF DAN EFISIEN DI INSTALASI RADIOLOGI - Widya Mufida; Muhamad Faik (Yayasan Wayan Marwan Pulungan, 2023)
Emergencies can be caused by disease, natural disasters and accidents. In the Radiology Installation, patients are no exception with emergencies that require immediate treatment due to trauma, illness or accidents experienced by the patient, apart from that the emergency situation that occurs in the Radiology Installation is that the patient has an allergic reaction to the contrast medium. The solution offered is training regarding handlers on radiographic examinations of emergency patients and first aid for patients who experience contrast media allergies. The training aims to improve soft skills and add insight to radiographers, alumni and D3 Radiology Study Program students by means of training in the effective and efficient handling of emergency patients at the Radiology Installation. From the results of the pretest and posttest, an increase of 20% was obtained, this shows success in increasing radiographers' understanding of handling patients in emergencies at radiology installations.